Turning employees into owners: An analysis of policy initiatives for rebuilding the American Dream. Issue 3 (12th November 2019) - Case, John; Quarrey, Michael
Abstract : Purpose: The purpose of this paper is to review and analyze policies where employee share ownership might be relevant to the inequality debate in the USA. Design/methodology/approach: Description and analysis of policy alternatives designed to increase the prevalence of employee ownership in the USA economy. Findings: Since 1974, Congress has passed many provisions to encourage employee ownership, all with widespread bipartisan support. Additional policies would have an even greater impact. Congress could "level the playing field" for corporate divestitures and sales of companies by private equity firms; create Employee Ownership Investment Corporations, modeled after Small Business Investment Corporations, to provide capital for sales to employees; and create an Employee Equity Loan Program to guarantee loans for employee-ownership transactions. Such measures would have no budgetary impact. It could also create tax incentives to encourage corporate and private-equity sales to employees and establish regulations to ensure that employee-owned companies are eligible for the full benefit of recent opportunity zone legislation. Legislation could also encourage publicly traded companies to offer stock to employees at a discount and require companies that receive various forms of special treatment from the government to establish employee stock-ownership programs. Originality/value: The academic journal literature has virtually no policy analyses on employee share ownership.